The role of Blastocystis hominis in the activation of ulcerative colitis - , Mehmet Kök, Yeşim Çekin, Ayhan Hilmi Çekin, Seyit Uyar, Ferda Harmandar, Yasin Şahintürk (Turkish Journal of Gastroenterology 1, 2019)
Background/Aims: Several studies have shown that a change in microbiota plays an important role in the pathogenesis of inflammatory bowel disease (IBD). Furthermore, with the emergence in recent studies of differences according to the subtype of IBD and whether the disease is active or in remission, there has started to be research into the relationship between IBD and several microorganisms. Blastocystis hominis is primary among these organisms. The aim of the present study was to determine the role of B. hominis in the acute flare-up of ulcerative colitis (UC). Materials and Methods: A total of 114 patients with UC were included in the study, with 52 in the active phase. The Mayo scoring system was used for the activity index. Patients determined with a flare-up agent other than B. hominis were excluded from the study. Fecal samples of the patients were examined by the polymerase chain reaction method for the presence of B. hominis. Results: B. hominis positivity was determined in 37 (34%) patients with UC. Of the patients, 17 (32.6%) were in the acute flare-up phase, and 20 (32.2%) were in remission (p=0.961). In 11 (64.7%) of the B. hominis positive patients, the disease severity was determined as mild-moderate (p<0.001). Conclusion: The results of the present study showed that while there was no difference between the active and remission phases in respect of B. hominis presence, there was milder involvement in those determined with B. hominis. Cite this article as: Cite this article as: Kök M, Çekin Y, Çekin AH, Uyar S, Harmandar F, Şahintürk Y. The role of Blastocystis hominis in the activation of ulcerative colitis. Turk J Gastroenterol 2019; 30: 40-6.